EVALUASI PENGELOLAAN LAHAN TERDEGRADASI TERHADAP SIFAT FISIKA TANAH PADA LAHAN REVEGETASI PASCATAMBANG BATUBARA - Ihsan Noor; Udiansyah Udiansyah; Bambang Joko Priatmadi; Emmi Winarni (EnviroScienteae, 2019)
One of the biggest challenges in coal mining activities is the successful management of degraded land through post-mining revegetation activities in accordance with applicable regulations. An easy way to assess the success of revegetation can be done with the approach of the physical properties of the soil. This study aims to evaluate post-mining revegetation land management by analyzing soil physical properties in the form of permeability and bulk density associated with plant growth. The research method was carried out by taking a predetermined sample in the plot area with a size of 20 x 20 m in each revegetation land planted with three depths are 0-20 cm, 20-40 cm, and 40-60 cm. The results showed that the success of revegetation land showed a positive increase where the growth of Acacia mangium plant height had reached 56.5% and the growth of the stem diameter of the plants had reached 53.8% when compared with the same plant type on the original revegetation land (HTI) according with the physical properties of the soil in the form of permeability which shows an increase and bulk density which shows a decrease approaching the value of the HTI land conditions. Thus, the success of post-mining land revegetation can be determined by the physical properties of the soil that affect the growth of the plant.